Development of user friendly e-lectures notes - Zeki, Akram M.; Rosdi, Iffah Nadhirah; Aszenan, Azliza; Hassan Abdalla Hashim, Aisha (IIUM Press, 2011)
The University of IIUM offers a multitude of relevant programs from the Foundation level to Bachelor Degree level to cater for the different needs of potential students. The foundation program prepares the students to embark on higher level of study at bachelor degree level while the diploma program is designed for dual path, i.e. students pursuing to bachelor degree level or students embarking on different profession. The reason for developing this website is to create new web-based system for the university system, to provide easiness in terms of selecting and combining one or more lecturers' schedule and view it in one timetable. In addition it will facilitate managing the course repository and records of the faculty without merging with others faculty's records.